Novel picornavirus in domestic rabbits (Oryctolagus cuniculus var. domestica) - Pankovics, Péter (Infect Genet Evol, 2016)
Picornaviruses (family Picornaviridae) are small, non-enveloped viruses with positive sense, single-stranded RNA genomes. The numbers of the novel picornavirus species and genera are continuously increasing. Picornaviruses infect numerous vertebrate species from fish to mammals, but have not been identified in a member of the Lagomorpha order (pikas, hares and rabbits). In this study, a novel picornavirus was identified in 16 (28.6%) out of 56 faecal samples collected from clinically healthy rabbits (Oryctolagus cuniculus var. domestica) in two (one commercial and one family farms) of four rabbit farms in Hungary. The 8364 nucleotide (2486 amino acid) long complete genome sequence of strain Rabbit01/2013/HUN (KT325852) has typical picornavirus genome organization with type-V IRES at the 5′UTR, encodes a leader (L) and a single 2A(H-box/NC) proteins, contains a hepatitis-A-virus-like cis-acting replication element (CRE) in the 2A, but it does not contain the sequence forming a “barbell-like” secondary structure in the 3′UTR. Rabbit01/2013/HUN has 52.9%, 52% and 57.2% amino acid identity to corresponding proteins of species Aichivirus A (genus Kobuvirus): to murine Kobuvirus (JF755427) in P1, to canine Kobuvirus (JN387133) in P2 and to feline Kobuvirus (KF831027) in P3, respectively. The sequence and phylogenetic analysis indicated that Rabbit01/2013/HUN represents a novel picornavirus species possibly in genus Kobuvirus. This is the first report of detection of picornavirus in rabbit. Further study is needed to clarify whether this novel picornavirus plays a part in any diseases in domestic or wild rabbits.